PSYCHOSOCIAL STRESSORS IN PATIENTS WITH CONVERSION DISORDER PRESENTING WITH NON EPILEPTIC FIT - Nazar, Zahid; Awan, Naila Riaz; Akhtar, Javaid (Journal of Postgraduate Medical Institute, 2011)
Objective: Material and Methods: Results: Conclusion: Significantly higher number of the patients presents with the stressor of troubles with in-laws, when assessed on the Holmes and Rahe social scale. Stressors were clearly identified in all patients. Ninety six (95.04%) out of the total 101 subjects had a history of stressors, while the rest 5 (4.95%) could not come up with any. The commonest stressors were Troubles with in-laws (21.78%), Major change in family get together (17.82%), Death of close family member (12.87%) respectively. This descriptive study was carried out at Lady Reading Hospital Peshawar Pakistan from January to June 2009. 101 consecutive patients with conversion disorder satisfying the inclusion and exclusion criteria were selected. They were interviewed by using Holmes and Rahe stress scale for the exploration of stressors and the results were analyzed from the entries in the Proform. To study the psychosocial stressors in patients with conversion disorder presenting with non epileptic fit.